Bedaquiline for the Treatment of Multidrug-resistant Tuberculosis in the United States. (26th September 2019) - Mase, Sundari; Chorba, Terence; Parks, Samuel; Belanger, Ann; Dworkin, Felicia; Seaworth, Barbara; Warkentin, Jon; Barry, Pennan; Shah, Neha
Abstract: Background: In 2012, the Food and Drug Administration approved use of bedaquiline fumarate as part of combination therapy for multidrug-resistant tuberculosis (MDR TB). We describe treatment outcomes, safety, and tolerability of bedaquiline in our case series. Methods: Data on patients started on bedaquiline for MDR TB between September 2012 and August 2016 were collected retrospectively through 4 TB programs using a standardized abstraction tool. Data were analyzed using univariate methods. Adverse events were graded using the Common Terminology Criteria for Adverse Events. Results: Of 14 patients, 7 (50%) had MDR, 4 (29%) had pre–extensively drug-resistant (XDR), and 3 (21%) had XDR TB. All had pulmonary TB, 5 (36%) had pulmonary and extrapulmonary TB, and 9/13 (69%) were smear positive. One patient (7%) had HIV coinfection, 5 (36%) had diabetes mellitus, and 5/14 (36%) had previous treatment TB. All patients were non–US-born and 5/14 (36%) had private insurance. All patients achieved sputum culture conversion within a mean of 71 days (26–116); 5 after starting bedaquiline. Twelve (86%) completed treatment and 1 (7%) moved out of the country. One patient (7%) had QTc prolongation >500 milliseconds and died 20 months after discontinuing bedaquiline of a cause not attributable to the drug. Common adverse events were peripheral neuropathy 7/14 (50%), not customarily associated with bedaquiline use, and QTc prolongation 6/14 (43%). Conclusions: Of 14 patients, 1 (7%) had an adverse event necessitating bedaquiline discontinuation. Safety, culture conversion, and treatment completion in this series (7%) support use of bedaquiline for the treatment of MDR/XDR TB. Abstract : Of 14 persons with multidrug-resistant tuberculosis (MDR TB) who received bedaquiline, 12 (86%) completed treatment, 1 (7%) moved, and 1 (7%) died of unrelated causes. Safety and treatment completion in this case series support use of bedaquiline for MDR TB treatment.